2017
DOI: 10.1039/c6cp07200c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and EPR-spectroscopic characterization of the perchlorotriarylmethyl tricarboxylic acid radical (PTMTC) and its 13C labelled analogue (13C-PTMTC)

Abstract: A hydrophilic tris(tetrachlorotriaryl)methyl (tetrachloro-TAM) radical labelled 50% with C at the central carbon atom was prepared. The mixture of isotopologue radicals was characterised by continuous wave and pulsed X-band electron paramagnetic spectroscopy (EPS). For the pharmaceutical and medical applications planned, the quantitative influence of oxygen, viscosity, temperature and pH on EPR line widths was studied in aqueous buffer, DMSO, water-methanol and water-glycerol mixtures. Under in vivo conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…Elewa et al reported a 50% enriched 13 C 1 -PTMTC which exhibits a doublet EPR spectrum in solution with an isotropic hyperfine coupling to the 13 C 1 of A iso = 83.5 MHz (29.82 G) 22 . This value is significantly higher than for the 13 C 1 -dFT analog (A iso =65.38 MHz, 23.35G) [10][11] which indicates a higher spin density at the central carbon for PTMTC than for the Finland trityl derivative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Elewa et al reported a 50% enriched 13 C 1 -PTMTC which exhibits a doublet EPR spectrum in solution with an isotropic hyperfine coupling to the 13 C 1 of A iso = 83.5 MHz (29.82 G) 22 . This value is significantly higher than for the 13 C 1 -dFT analog (A iso =65.38 MHz, 23.35G) [10][11] which indicates a higher spin density at the central carbon for PTMTC than for the Finland trityl derivative.…”
Section: Resultsmentioning
confidence: 99%
“…However, the anisotropic values of the hyperfine interaction were not reported. 22 To get insight into the anisotropy of the 13 C 1 hyperfine interaction , we performed a density functional theory calculation at the B3LYP level using the IGLO-III basis sets, specially tailored for the calculation of EPR properties (Table 1 and SI). The calculated isotropic hyperfine splitting of A iso (C 1 ) = 77.6 MHz is in good agreement with the experimental value of 83.5 MHz.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the anisotropy of the hyperfine splitting and the effect of viscosity on t R were not provided. [21] Dissolved oxygen is also known to broaden the linewidth of TAM radicals through the Heisenberg spin exchange. However, the sensitivity of TAMs to oxygen is much smaller.…”
Section: Angewandte Chemiementioning
confidence: 99%